1990
DOI: 10.1017/s0022112090000441
|View full text |Cite
|
Sign up to set email alerts
|

One-dimensional vibratory instability of planar flames propagating in tubes

Abstract: A complete analysis of the one-dimensional vibratory instability of planar flames of premixed gases propagating in tubes is provided. The driving mechanism results from unsteady coupling between flame structure and acoustic waves through temperature fluctuations. In certain conditions, the strength of such an instability will be proved to be sufficiently strong to produce large-amplitude fluctuations as soon as the flame has travelled a distance of the order of the acoustic wavelength. Stability limits and tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(88 citation statements)
references
References 9 publications
(16 reference statements)
9
79
0
Order By: Relevance
“…In this section, we review previously proposed mechanisms [8,11] for the generation of primary acoustic instability for propagating flames in tubes. Here, two different coupling mechanisms characterizing the feedback mechanism of the acoustic instability on flame fronts are introduced.…”
Section: Coupling Mechanisms Of Primary Acoustic Instabilitymentioning
confidence: 99%
See 3 more Smart Citations
“…In this section, we review previously proposed mechanisms [8,11] for the generation of primary acoustic instability for propagating flames in tubes. Here, two different coupling mechanisms characterizing the feedback mechanism of the acoustic instability on flame fronts are introduced.…”
Section: Coupling Mechanisms Of Primary Acoustic Instabilitymentioning
confidence: 99%
“…An approach toward resolving this issue has generally been to consider the Rayleigh criterion [5]: an acoustic wave will be amplified if a time integral of the product of pressure and heat release fluctuations is positive over a pressure cycle. Considering this criterion, many previous researchers [6][7][8][9][10][11][12] have proposed various mechanisms on primary acoustic instability. We can classify them into two large groups depending whether they are related to coupling of the acoustic Initially, Dunlap [7] theoretically showed that the effect of the pressure and adiabatic temperature of an incoming acoustic wave modulates local heat release rates of a flame with the correct phase relationship.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A general asymptotic theory was presented by Wu, Wang, Moin & Peters (2003) (referred to as WWMP hereafter) to describe the acoustic-flow-flame coupling in the 'corrugated flamelet' regime. Using this general formulation, they provide a unified description of the flame-acoustic coupling mechanisms of Clavin et al (1990) and Pelce & Rochwerger (1992).…”
Section: Premixed Combustion and Instabilitymentioning
confidence: 99%